5-Aminolevulinic Acid (5-ALA) Use at The Walton Centre NHS Foundation Trust (WCFT). (1st October 2022) - Bennett, Ruth; Akinsanya, Elizabeth
Abstract: AIMS: To audit the use of 5-ALA at WCFT to determine adherence to NICE guidance [NG99] and the Trust guideline. METHOD: Data was retrospectively evaluated from 77 patients prescribed 5-ALA at WCFT Jan 2020 – Jan 2022. RESULTS: Of the 77 patients, 61 (79%) patients had 5-ALA induced fluorescence documented intraoperatively which aided resection and 7 patients (9%) had no confirmed fluorescence. In patients with no fluorescence noted, the administration time to operation time was variable. The remaining 9 patients (12%) had no documentation on the presence or absence of fluorescence. Prior to surgery, 67 patients had an MDT outcome of likely high grade glioma. 66 patients had this confirmed with histology post-surgical resection. The remaining patients had various MDT diagnosis documented including oligoastrocytoma, oligodendroglioma and lesion. 87% of patients had the correct dose of 20mg/kg prescribed. 14 patients (18%) did not have liver function tests (LFT) checked during admission as per Trust policy. Of those checked, 29 patients (37%) had new derangement of LFT. CONCLUSION: The use of 5-ALA has aided surgical resection, enabling greater resection in the majority of patients prescribed for at WCFT. It has been used in accordance with NICE for HGG resections in 87% of cases. Some improvement could be made in ensuring the correct dose is prescribed and the appropriate monitoring (LFT) is carried out post procedure. Theatre documentation could be improved so future audit can more easily identify extent of resection and extent of fluorescence.